Analysis of solvency and loss of asset value in publicly traded Tanker shipping firms - Hameed Misbahuddin Rowther Mohidin Pitchai (2018)
Research findings have shown that there was an ample amount of available cash at low interest rates during the economic boom in 2006 and 2007. Thus, investors, banks and shipping companies pumped hundreds of billions into the shipping business with the hope of yielding a high return. Subsequently, many shipping companies have massively invested in new ships building during this period. However, it takes 3-5 years to deliver the new build ship. By then, the shipping industry is facing with an economic downturn whereby the demand for shipping goods plumped drastically, leaving the market with overcapacity of ships. Therefore, the purpose of this paper was to conduct a financial analysis of the shipping companies by focusing on their liquidity, solvency and ship asset impairment loss using ratio analysis. Data for the study covered the period 2006-2016 and was obtained from the annual report of the publicly traded shipping firms. This study explores the financial structure of 5 shipping firms from the tanker industry. It also compares the financial ratios of the sampled shipping firms with the industry average provided by the PricewaterhouseCoopers (PwC). The result shows the performance of the selected companies with the rest of the industry. We aim to study the solvency of the shipping firms by mainly analysing their Current ratio, Cash ratio, Total Debt ratio and Debt-equity ratio. This will give us a better idea on the performance of the selected companies. By comparing with the industry average performance, we will be able to better understand their financial performance and how they managed to ‘ride the storm’ during the tough economy. We are also formulating a model which will aid companies to calculate the industry averages without the PwC data.The second part of our report will involve the loss of asset values of the selected companies. This is usually referred to as ‘impairment loss’ in the financial statements. In recent studies, the impact of impairment loss has often been overlooked. As the main assets of ship owning firms is the ships, an impairment loss declared will lower the value of the non-current assets of that company in the financial statements. This will reduce the total debt ratio of the company. This would result in the ability of the company to service its debts via its assets to fall. Furthermore, as ships are usually financed by bank loans, a huge impairments loss would allow the banks to regain possession of the ships from the firms to be auctioned off as the value of the assets must be at least 120% of the loan or higher. When it drops to below that value, banks can gain control and auction the asset off to collect their loan payments.